Corporate Social Responsibility: The Good, the Bad and the Ugly - Banerjee, Subhabrata Bobby (Critical sociology, 2008)
In this article I critically analyze contemporary discourses of corporate social responsibility and related discourses of sustainability and corporate citizenship. I argue that despite their emancipatory rhetoric, discourses of corporate citizenship, social responsibility and sustainability are defined by narrow business interests and serve to curtail interests of external stakeholders. I provide an alternate perspective, one that views discourses of corporate citizenship, corporate social responsibility, and sustainability as ideological movements that are intended to legitimize and consolidate the power of large corporations. I also problematize the popular notion of organizational `stakeholders'. I argue that stakeholder theory of the firm represents a form of stakeholder colonialism that serves to regulate the behavior of stakeholders. I conclude by discussing implications for critical management studies.